You can expand as I showed you earlier. Expand both expressions and you'll get the same final expression.
Hi guys,i had posted a few threads on algebra just now.
There are many solution but i find the one which i could understand was:
Question: Factorise 121 - (p+2)Square
Answer/Solution: But, what i don't understand is this solution:
Question: Factorise 121 - (p+2)Square
Answer/Solution: 121 - (p)Square + 2(p)(2) + 2Square
= 121 - (p)Square + 4p + 4
= 117 - (p)Square + 4p
= (9-p)(13+p)
I mean, how do you know if it's "(9-p)(13+p)" ?
Thank you so much for your time
Well, what I initially meant is:
11^2 - (p+2)^2 = 121 - p^2 - 4p - 4 = 117 - p^2 - 4p
And taking the other,
(9-p)(13+p) = 117 - p^2 - 13p + 9p = 117 - p^2 - 4p
Which is the same as before. Hence, both are equivalent, meaning that the answer (9-p)(13+p) is correct.